Uncommon complication in traumatic ACL rupture: Tibial neuropathy due to popliteus muscle haemorrhage: A case report - Maarten Rombauts; Arne Hautekiet; Koen Matthys; Willem Goethals (Journal of Orthopaedic Reports)
Background: Popliteus muscle haemorrhage is a rare cause of tibial mononeuropathy after severe knee trauma. Case report: 57-year-old patient with left knee trauma presented with knee instability, sensory loss over the sole of the foot and a partial foot plantar flexion and complete toe flexion paralysis. MRI demonstrated an acute ACL rupture combined with a popliteus muscle hematoma causing compression of the tibial nerve just distal to the popliteal fossa. Tibial nerve continuity was preserved on MRI and on ultrasound. Nerve conduction study showed a progressive decline to zero in CMAP amplitude of the tibial nerve, corresponding with total axonotmesis. There was no contraction in the most distal tibial nerve innervated musculature on EMG, with sparing of the gastrocnemius muscle. Conservative treatment consisting of a patient-tailored rehabilitation program was chosen. There was a functional recovery at 1-year follow-up, but remaining toe spreading paralysis and sensory disturbances. Conclusion: Conservative treatment for tibial neuropathy due to popliteus muscle haemorrhage has a good functional outcome, in which EMG can help estimate the prognosis. Operative release should be considered when there is unbearable pain, progressive neurological deterioration, clear vascular compression or loss of nerve continuity.